Role of Accurate Assessment of Nutritive Value in Exploring Food and Nutritional Status Relationships: Observation from A Pre-School Child Study Conducted in Karachi Pakistan - Hakeem, Rubina (Nurture, 2013)
It is hypothesized that relationship between diet and nutritional status could be masked by ignoring variation in cooking methods in certain communities. This study was planned to test the above s hypothesis by studying the association between diet and nutritional status of children, by identifying variations in nutritive value of home cooked Lentils. From the data collected for a larger cross sectional study samples of home cooked dals and information about nutritional status of pre-school children was used from 51 lower middle class households. Lab analyzed values were higher for moisture and fat and lower for protein, as compared to the Pakistani food composition tables (PFCT) A positive relationship (r= 0.335) with a(P<0.05), suggested an association between the MUAC of children and the percentage of calories coming from protein in dals in our study children. No such association was observed when values given in PFCT were used. These observations indicate that for valid assessment of association between composition of home cooked foods and nutritional status of children, use of generalized information given in national food composition tables be may not be inaccurate.